CLAY MINERALOGY OF THE CRETACEOUS STRATA OF THE BRITISH ISLES - Jeans C.V. (My University, 2006)
The clay mineralogy of the Cretaceous strata of the British Isles is described and discussed within its lithostratigraphical and biostratigraphical framework using published and unpublished sources as well as 1400 new clay mineral analyses. The regional clay mineral variation is described systematically for the following strata: (1) Southern England - Purbeck Limestone Group (Berriasian/Ryazanian; Lulworth and Durlston formations), Wealden Group (Valanginian-Barremian/ Aptian; Ashdown, Wadhurst Clay, Tunbridge Wells Sands, Grinstead Clay Member, Wealden Clay, Wessex and Vectis formations), Lower Greensand (Aptian-Lower Albian; Atherfield Clay, Hythe, Sandgate, Folkestone Sands, Ferruginous Sands, Woburn Sands and Faringdon Sponge Gravels formations), Selborne Group (Middle-Upper Albian; Gault Clay and Upper Greensand formations) and the Chalk Group (Cenomanian-Lower Maastrichtian). (2) Eastern England - Cromer Knoll Group (Ryazanian-Upper Albian; Speeton Clay, Spilsby Sandstone, Sandringham Sands, Claxby Ironstone, Tealby, Roach Ironstone, Dersingham, Carstone and Red Chalk (or Hunstanton Red Limestone) formations). (3) Scotland - Inner Hebrides Group (Cenomanian-Campanian; Morvern Greensand, Gribun Chalk, Coire Riabhach Phosphatic Hibernian Greensands formations). (4) Northern Ireland - Hibernian Greensands (Cenomanian-Santonian) and Ulster White Limestone formations (Santonian-Lower Maastrichtian). The stratigraphical patterns of clay mineral variation divide naturally into two types; firstly, the more complex pattern of the Lower Cretaceous strata and secondly, the simple pattern of the Upper Cretaceous. Clay mineral variations in the non-marine and marine Lower Cretaceous strata of England are best explained by the interplay of two main clay mineral assemblages between which all gradations occur. The assemblage which dominates the main clay formations consists of mica, kaolin and poorly defined mixed-layer smectite-mica-vermiculite minerals, and sometimes includes vermiculite and traces of chlorite. It is dominantly of detrital origin and detailed evidence indicates it is derived largely from the reworking of Mesozoic sediments although ultimately from weathered Palaeozoic sediments and metasediments. Although mainly of detrital origin, this assemblage contains a persistent component that formed coevally with the approximate depositional age of its host sediment. Whether this component is of soil origin or was neoformed in the sediment shortly after deposition is unclear. There is little firm evidence indicating the sources of this clay mineral detritus. However, in the strata of the Wealden Group of southern England, mineral trends suggest three sources; one of these was to the west (Cornubian Massif), another must have been the Anglo-Brabant landmass. In the Selborne Group (Middle-Upper Albian) and in the overlying Lower Chalk (Cenomanian) where this assemblage makes its last appearance in the Cretaceous of England, there is good evidence of easterly and south-easterly sources. The second main assemblage tends to be largely monominerallic, and usually dominated by smectite with or without small amounts of mica; less frequently, kaolin, berthierine or glauconite sensu lato is the sole or dominant component. It is considered to be of volcanogenic origin, derived from the argillization of volcanic ash under different conditions of deposition and diagenesis. The source of the ash in Berriasian-Aptian times seems to have been an extensive volcanic field in the southern part of the North Sea and in the Netherlands, whereas in the Albian (and extending into the Cenomanian) a westerly source dominated. The current controversy about the role of climate or pattern of volcanic activity controlling the clay mineral stratigraphy of the Lower Cretaceous is reviewed. In the lower part of the Upper Cretaceous strata of England, Scotland and Ireland, sand-grade glauconite is particularly abundant. Much of it represents the glauconitization of pene-contemporanous volcanic ash, possibly of basaltic origin, associated with continental breakup and the opening up of the Atlantic Ocean and the earliest stages in the development of the Hebridean Tertiary Igneous Province. The Upper Cretaceous Chalk facies of England and Ireland is dominated by a smectite-rich clay assemblage containing mica, and the various hypotheses for its origin (detrital, neoformation, volcanogenic) are reviewed in the light of available mineralogical, chemical and geological data. © 2006 The Mineralogical Society.
Keywords: BRITISH ISLES; CLAY MINERALOGY; CRETACEOUS; Мезозой::Меловая; Mesozoic::Cretaceous